2015
DOI: 10.1080/21693277.2015.1094756
|View full text |Cite
|
Sign up to set email alerts
|

End mill tools integration in CNC machining for rapid manufacturing processes: simulation studies

Abstract: Computer numerical controlled (CNC) machining has been recognized as a manufacturing process that is capable of producing metal parts with high precision and reliable quality, whereas many additive manufacturing methods are less capable in these respects. The introduction of a new layer-removal methodology that utilizes an indexing device to clamp the workpiece can be used to extend CNC applications into the realm of rapid manufacturing (CNC-RM) processes. This study aims to improve the implementation of CNC m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In 2015, Osman Zahid et al found out that the capability of CNC for the rapid machining operation can be improved by using dissimilar end mill tools for finishing. They introduced a new layer removal methodology in which an indexing device is used to clamp the workpiece and an SSF to hold the part during rapid machining [16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2015, Osman Zahid et al found out that the capability of CNC for the rapid machining operation can be improved by using dissimilar end mill tools for finishing. They introduced a new layer removal methodology in which an indexing device is used to clamp the workpiece and an SSF to hold the part during rapid machining [16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of additive techniques enables the production of objects with complex and irregular shapes, which is very often impossible in the case of other technologies. However, due to the high level of integration of computer systems into production processes in the era of Industry 4.0 [ 9 ], the term rapid prototyping and tooling should be considered as a broader concept, because its components are often directly or indirectly related to other forms of production, such as computer numerical control (CNC) machining (through the integration of CAD/CAM environments) [ 10 ], reverse engineering (3D scanning) [ 11 ] or investment casting (making disposable casting patterns) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%